Dissecting the mechanism of regulation of a ferroptosis-like form of cell death in Drosophila melanogaster - Saini, Sanjay; Owusu-Ansah, Edward (Frontiers in Cell Death, 2023)
Ferroptosis is a specific form of non-apoptotic cell death that is driven by iron-dependent phospholipid peroxidation. Research over the past decade has contributed to our understanding of how this important cell death process is regulated in mammalian systems, especially with regard to the distinct modes of induction, the role of metabolic signals, the organelles involved, implications of ferroptosis for development and aging, and how our improved understanding of the process can be exploited for therapeutic purposes. Other studies have described variants of this ancient cell death process in cyanobacteria, plants and protozoans. Emerging evidence indicates that a ferroptosis-like form of cell death exists in fruit flies (Drosophila melanogaster). Due to the extensive homology of genes in Drosophila melanogaster and Drosophila suzukii, unique aspects of ferroptosis in Drosophila melanogaster may be of particular relevance for developing targeted pesticides against D. suzukii – a major invasive agricultural pest of the berry and wine industry in Southeast Asia, Europe and America. Further, aspects of ferroptosis in Drosophila melanogaster that are conserved in insects in general may provide the basis for identifying new insecticides for controlling the spread of vector-borne diseases such as malaria. In this perspective, we highlight some of the studies in Drosophila melanogaster that have sought to improve our understanding of the ferroptosis-like form of cell death that operates in this organism and conclude with a discussion of the opportunities and challenges for studying this phenomenon in fruit flies.